Non-syntrophic reactions in anaerobic unsaturated LCFA conversion by methanogenic sludges - Cavaleiro, A. J. (2013)
Lipids are energy-rich compounds. This energy can be conserved as biogas in anaerobic bioreactors but the process is frequently hindered by long-chain fatty acids (LCFA) accumulation. LCFA catabolism is thought to occur via beta-oxidation, performed by anaerobic bacteria that live in obligatory syntrophy with H2 consuming methanogens, but the initial steps of unsaturated LCFA biodegradation are still unclear. In this work we hypothesize that these initial steps do not depend on interspecies H2 transfer. To test this, six anaerobic bioreactors were continuously fed with saturated or unsaturated C16- and C18-LCFA, and operated in the presence or absence of bromoethanesulfonate, a selective inhibitor of methanogens. Intermediates of LCFA degradation including long- and medium-chain fatty acids, volatile fatty acids and methane were monitored. Bacterial community composition was analysed in the different bioreactors by denaturing gradient gel electrophoresis of 16S rRNA reverse transcriptase-PCR products. In the presence or absence of the inhibitor of methanogenesis, palmitate (C16:0) accumulated during the degradation of oleate (C18:1), accounting for more than 50% of total accumulated LCFA. Palmitoleate (C16:1) feeding resulted in the build-up of myristate (C14:0) and palmitate (C16:0). Accumulation of saturated intermediary-LCFA was two to four times higher in bioreactors in which methanogenesis was inhibited compared to methanogenic bioreactors. Beta-oxidation of saturated intermediates only occurred in methanogenic bioreactors. No catabolic activity was observed in the bioreactor fed with saturated LCFA when methanogenesis was inhibited. These results show that the first steps of unsaturated LCFA degradation are not obligatorily syntrophic, and suggest that beta-oxidation is the limiting step in the overall conversion of LCFA to methane.